2010
DOI: 10.1093/chemse/bjp095
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of the 3 G-Protein Subunits, Gα, Gβ, and Gγ, in the Olfactory Receptor Organs of Adult Drosophila melanogaster

Abstract: In many species, olfactory transduction is triggered by odorant molecules that interact with olfactory receptors coupled to heterotrimeric G-proteins. The role of G-protein-linked transduction in the olfaction of Drosophila is currently under study. Here, we supply a thorough description of the expression in the olfactory receptor organs (antennae and maxillary palps) of all known Drosophila melanogaster genes that encode for G-proteins. Using RT-polymerase chain reaction, we analyzed 6 Galpha (G(s), G(i), G(q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 46 publications
2
43
0
1
Order By: Relevance
“…In particular, experimental evidence suggests that conventional ORs of D. melanogaster and A. gambiae also exhibit such an inverted topology compared to the canonical N out -C in 7TM topology of the GPCR family of mammalian ORs (Benton et al 2006;Smart et al 2008;Tsitoura et al 2010). Although insect ORs adopt an olfactory signaling strategy distinct from GPCRs due to this structural difference, a number of reports suggest that G-protein-mediated second messenger pathways are likely to be involved in olfactory transduction because different G-protein subunits are expressed in insect ORNs and olfactory perception can be modified through affecting the cAMP and IP3 pathways (Martin et al 2001;Gomez-Diaz et al 2004;Rützler et al 2006;Kain et al 2008;Wicher et al 2008;Boto et al 2010).The group of threonines (T) and tyrosines (Y) are extremely conserved in the region of TM VII (Fig. 1, box).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, experimental evidence suggests that conventional ORs of D. melanogaster and A. gambiae also exhibit such an inverted topology compared to the canonical N out -C in 7TM topology of the GPCR family of mammalian ORs (Benton et al 2006;Smart et al 2008;Tsitoura et al 2010). Although insect ORs adopt an olfactory signaling strategy distinct from GPCRs due to this structural difference, a number of reports suggest that G-protein-mediated second messenger pathways are likely to be involved in olfactory transduction because different G-protein subunits are expressed in insect ORNs and olfactory perception can be modified through affecting the cAMP and IP3 pathways (Martin et al 2001;Gomez-Diaz et al 2004;Rützler et al 2006;Kain et al 2008;Wicher et al 2008;Boto et al 2010).The group of threonines (T) and tyrosines (Y) are extremely conserved in the region of TM VII (Fig. 1, box).…”
Section: Discussionmentioning
confidence: 99%
“…The Giknockdown condition showed no effect on synapse number (Fig. 5C) and Cta, whose sequence is rather divergent from the rest of Ga subtypes (Boto et al, 2010), also yielded no effect (Fig. 5C).…”
Section: Ric8a Regulates Synapse Number Through Ga Protein Activitymentioning
confidence: 91%
“…The second messenger 3′,5′-cyclic adenosine monophosphate (cAMP) is an activating ligand for Orco channels (Wicher et al, 2008;Stengl, 2010;Stengl and Funk, 2013) and has been shown to enhance the activity of olfactory sensory neurons (OSNs) that express ORs (Olsson et al, 2011;Getahun et al, 2013). Insect OSNs possess the cellular machinery required to produce cAMP (Iourgenko and Levin, 2000;Boto et al, 2010) and disruption of this signaling cascade has been reported to affect the functional properties of OSNs (Martín et al, 2001;Gomez-Diaz et al, 2004;Deng et al, 2011). However, insect ORs show an inverted topology with respect to their mammalian counterparts (Benton et al, 2006), they are not related to any known G protein-coupled receptor and there is no proof of a direct interaction between insect ORs and G proteins.…”
Section: Introductionmentioning
confidence: 99%